Liposomal sphingomyelin influences the cellular lipid profile of human lymphoblastic leukemia cells without effect on P-glycoprotein activity - Zembruski, Nadine Cécile Luise; Theile, Dirk; Burhenne, Jürgen; Haefeli, Walter E.; Weiß, Johanna (Molecular pharmaceutics, 2013)
Sphingomyelin (SM)/cholesterol liposomes are currently investigated as drug carriers in cancer therapy. However, no data is available on the influence of SM itself on P-glycoprotein (P-gp) mediated multidrug resistance. P-gp is at least partly located in sphingolipid-enriched lipid raft domains of the plasma membrane, and its activity depends on the lipid profile of the membrane, which could be altered by therapeutical SM liposomes. Therefore, the aim of this study was to analyze the effect of liposomal SM on P-gp activity, P-gp distribution in microdomains, SM content of the membrane domains, and sensitivity of human lymphoblastic CEM cells toward cytotoxic drugs in vitro. Assays were conducted in CEM and multidrug resistant CEM/ADR5000 cells. SM-only liposomes were prepared by a newly developed ethanol injection protocol and thoroughly characterized. Inclusion of SM into the membrane was analyzed by fluorescence microscopy and flow cytometry. Influence of SM liposomes on P-gp activity was assessed by rhodamine efflux and calcein assay, and sensitivity toward cytotoxic drugs was analyzed by flow cytometric 7-AAD staining. Influence on P-gp distribution was analyzed by Western blot after density gradient centrifugation. SM 16:0, 18:0, and 24:1 were quantified by liquid chromatography coupled to tandem mass spectrometry. P-gp was mainly located in nonraft fractions, which did not change upon liposome treatment. Liposomes increased SM 16:0 and SM 24:1 content in nonraft domains, but not in raft domains of multidrug resistant cells. SM-only liposomes did not influence P-gp activity and chemosensitivity. In conclusion, SM-only liposomes in therapeutic amounts did not influence P-gp mediated multidrug resistance in CEM cells.
Gesehen am 27.07.2021